HUMAN BREAST MILK FORTIFICATION WITH SKIMMED MILK AND OLIVE OIL FOR WEIGHT GAIN IN VERY LOW BIRTH WEIGHT NEONATES - Arouj Waqqas; Zeeshan Ahmed; Huma Farrukh; Hina Khalid; Talal Waqar (Pakistan Armed Forces Medical Journal, 2021)
Objective: To observe the effect of fortification of expressed human breast milk with olive oil and skimmed milk in improving weight gain in very low birth weight neonates and shortening their length of hospital stay.